Determinants of market capitalization of listed firms: evidence from an emerging country - Dinh Nguyen Phan; Thi Nhat Minh To (Journal of Economics and Development)
Purpose – This study investigates the determinants of the market capitalization of listed companies through evidence from an emerging country. Design/methodology/approach – This research employs the system generalized method of moments for a dataset of 7,608 observations from 687 Vietnamese listed firms. Findings – Our findings show that both external and internal factors affect market capitalization. Intellectual capital, sales growth, profit, leverage and crises are positively linked to market capitalization; meanwhile, foreign direct investment, inflation and gross domestic product negatively affect market capitalization. The negative effect of macrofactors reflects the fact that the macroeconomic environment can deteriorate investment values and then market capitalization. This implies that macroeconomic stability is very crucial for firms and financial stability. The COVID-19 and financial crisis have a moderating influence on market capitalization through sales growth, profitability and leverage. Unlike previous studies, we find that intellectual capital plays a very essential role regardless of whether there is a crisis or not. Therefore, firms should focus on intellectual capital to grow market capitalization sustainably. Originality/value – This paper contributes to the literature of market capitalization by investigating the determinants of market capitalization with a joint assessment of the financial crisis and the COVID-19 pandemic, which have not yet been considered together in previous studies. It enriches the literature by investigating the moderating effect of COVID-19 and financial crisis on the relationships between some key determinants and market capitalization. Unlike previous studies, our study highlights the essential role of intellectual capital in enhancing market capitalization regardless of whether there is a crisis.